2018
DOI: 10.1002/cpt.1017
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Opportunities With Oncology Drug Development in China

Abstract: Cancer is a growing public health problem in China. Despite the high unmet medical need of patients with cancer in China, oncology drug approvals have historically lagged behind those in the West, mainly the United States and Europe. China is currently undertaking regulatory reforms at a fast pace in order to mitigate this lag.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 64 publications
1
30
0
Order By: Relevance
“…Approvals of small molecules in Japan and China have occurred on average 2.3 and 3.3 years after their approvals in the United States, whereas the approval delays of biologics are 2.8 and 4.8 years in Japan and China, respectively. The delays in drug approval remain a potential issue on patient health in China and Japan …”
Section: Drug Approval Delaymentioning
confidence: 99%
See 2 more Smart Citations
“…Approvals of small molecules in Japan and China have occurred on average 2.3 and 3.3 years after their approvals in the United States, whereas the approval delays of biologics are 2.8 and 4.8 years in Japan and China, respectively. The delays in drug approval remain a potential issue on patient health in China and Japan …”
Section: Drug Approval Delaymentioning
confidence: 99%
“…Biologic drugs, including monoclonal antibodies, are mainly distributed to the blood and basically eliminated by nonspecific immunoglobulin G and specific target‐mediated drug disposition pathways via intracellular catabolism . Their clearances are generally not influenced by the polymorphism of metabolic enzymes and less sensitive to intrinsic ethnic factors.…”
Section: Elimination Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Thus, the association of lower body weight with increased exposure and potentially associated safety risks may be more relevant for Chinese patients compared with Western populations. 23 However, the efficacy is not expected to be reduced given higher exposure with flat dosing. 6,8 A pooled PPK analysis of data from global studies showed that the time-averaged steady-state exposure of nivolumab 240 mg was consistent with 3 mg/kg every 2 weeks across multiple tumor types.…”
mentioning
confidence: 99%
“…Besides intrinsic factors, an extrinsic factor resulting in ethnic differences important in China is the culture of using botanical preparations (Bajaj et al 2019). Several preparations used in traditional Chinese medicine (TCM) have been reported to alter enzyme activities in preclinical models and/or in clinical drug-drug interaction studies (Qiu et al 2016;Tang et al 2016).…”
Section: Use Of Pbk Modelling To Study Inter-ethnic Human Kinetic Differencesmentioning
confidence: 99%